Minha experiência cursando medicina na UFSCar: uma narrativa crítico-reflexiva - Silva, Ana Beatriz Lima e (Universidade Federal de São Carlos, 2024)
The UFSCar Medicine course requires graduating students to complete a Course Conclusion Paper (TCC), which will be prepared here in accordance with the guidelines of the Pedagogical Political Project (PPP) in the form of a critical-reflexive narrative about a student's experience, in this degree, reporting the subjectivities of this experience. Here I will develop in a chronological line, following the three cycles of medical training, each lasting two years.
My experience studying medicine at UFSCar: a critical-reflexive narrative
Keywords: Medicina; Narrativa crítico reflexiva; Medicine; Critical-reflexive narrative; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA